Navigating Uncertainty in A Digital Age: Cognitive Mechanisms Behind Doomscrolling in Indonesia - Ezraputi Salsabila; Novi Qonitatin (Green Publisher, 2025)
The rise of doomscrolling has raised concerns about its psychological impact, particularly among digital-native populations like Generation Z. In the Indonesian context, where sociocultural pressures intersect with high digital media exposure, this behavior becomes increasingly relevant. The objective of this study is to examine how doomscrolling behavior is driven and maintained by Intolerance of Uncertainty (IoU), a psychological construct that reflects individuals’ difficulty in managing ambiguous or unpredictable situations. By employing a narrative literature review approach, this paper synthesizes interdisciplinary sources from psychology, media studies, and behavioral science to explore the mechanisms, characteristics, and cultural dimensions of doomscrolling among Indonesian youth. Sources were gathered from databases such as PubMed, APA PsycNet, ScienceDirect, and Google Scholar, focusing on recent publications between 2015 and 2025. The review finds that high levels of IoU predict compulsive information seeking and rumination, which are core features of doomscrolling. Furthermore, doomscrolling appears to function as an emotion regulation strategy that paradoxically intensifies anxiety and cognitive overload. Sociocultural factors such as academic pressure, emotional avoidance, and collectivist values also contribute to the internalization of distress, making digital engagement a substitute for emotional expression. These findings highlight the urgency of integrative interventions to reduce the psychological burden of uncertainty in the digital age, especially for Gen Z in Indonesia.